Law, Community and Ultima Ratio in Transnational Law - Massimo Fichera (Oñati Socio-Legal Series)
The paper aims to examine the concept of transnational law and the way market forces affect the notion of community at the transnational level. Can the principle of ultima ratio operate in this context and how should this occur? Recent events, including the expansion of the anti-money laundering legislation and the measures enacted following the economic crisis, will be used as emblematic cases illustrating the development of transnational law and its impact on society. The analysis will also focus on a general discussion on whether the market can be considered an integral part of a transnational community and the extent to which principles and ideas generated in criminal law can contribute to a community-oriented approach.